Handling Viral Cases On Social Media By The Police Public Relations (Case Study: Vina Cire) - Fauzi Surya Chandra (Jurnal Indonesia Sosial Sains, 2025)
This study investigates the communication strategy employed by the Public Relations Division (Humas) of the Indonesian National Police in handling viral crises on social media, focusing specifically on the Vina Cirebon case. Utilizing a qualitative descriptive approach, this research was conducted through in-depth interviews, document analysis, and media observation involving key stakeholders, including police officers, journalists, and digital communication analysts. The findings reveal that Humas Polri exhibited weak crisis preparedness, evident from the lack of early detection systems, risk profiling, and crisis-sensing capabilities. During the crisis period, the institutional response was characterized by delays, inconsistencies in official statements, and limited coordination between headquarters and regional police units. The study also found underutilization of social media platforms, which led to unaddressed public speculation and the dominance of alternative narratives. Moreover, the communication strategy applied did not fully align with the Situational Crisis Communication Theory (SCCT), as Polri tended to employ defensive rather than accommodative or restorative approaches. This condition ultimately led to a decline in public trust and institutional legitimacy. The study contributes to the field of police science and public relations by highlighting the urgency of integrated crisis communication strategies, particularly in managing public perception in the digital age.